PENGARUH KUALITAS LABA DAN LIKUIDITAS SAHAM TERHADAP BIAYA MODAL EKUITAS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Mia Efrina; Faisal Faisal (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research aims to empirically examine the effect of earnings quality, stock liquidity on cost of equity capital in manufacturing companies in Indonesia. This research uses earnings management as indicators of earnings quality and trading volume as indicators of stock liquidity. The sampling method used in this research is purposive sampling method, it is a method that  take sampling based on specific criteria. So, there are 20 manufacturing  companies selected as the sample which are further analyzed by multiple regression to investigate the partial and simultaneous effects. It was found that, the partial earnings management is a significant positive effect on cost of equity capital and trading volume is a significant negative effect on cost of equity capital. It is found that the simultaneous testing of earnings management and trading volume have a significant effect on cost of equity capital. Keywords: Earning Quality (Earnings Management), Stock Liquidity (Trading Volume), Cost Of Equity Capital.  136